A fotografia no sistema de informação Marques da Silva/Moreira da Silva: uma abordagem sistémica - Costa, Sofia Elisabete Nogueira (Revelar: Revista de Estudos da Fotografia e Imagem, 2018)
In this scientific article we intend to approach the treatment of the Family Photography of the Information System Marques da Silva/Moreira da Silva. This work is based on a project developed within the scope of a master's thesis - presented to the Faculty of Arts of the University of Porto in 2014 - entitled "The Family Photography on the Information System Marques da Silva/ Moreira da Silva: a systemic approach". According to the concept of heritage presented by Laurajane Smith on her book Uses of Heritage - the relevance of the Marques da Silva family justifies the classification of photography as Cultural Heritage, that should be managed, protected and shared. Working with this concept and with other concepts related with the Information Science and with the Systemic Theory, we proceed to the treatment of family photography, to its integration in the Information System Marques da Silva!Moreira da Silva and its online availability through the archival management software AToM. Regarding the treatment and dissemination of the Marques da Silva Family Photography, it was necessary to establish a legal framework to determine which photographs could be released. Regarding the Portuguese legislation - the Direitos de Autor e Direitos Conexos, C6digo Civil, Constituic;iio da Republica Portuguesa, Lei Nacional de Protec;iio de Dados, Lei 67/98 de 26 de outubro- were analyzed. The photographic archive can be consulted here.